De Novo Design and Evolution of Artificial Disulfide Isomerase Enzymes Analogous to the Bacterial DsbC - Arredondo, Silvia (American Society for Biochemistry and Molecular Biology, 2008)
The Escherichia coli disulfide isomerase, DsbC is a V-shaped homodimer with each monomer comprising a dimerization region that forms part of a putative peptide-binding pocket and a thioredoxin catalytic domain. Disulfide isomerases from prokaryotes and eukaryotes exhibit little sequence homology but display very similar structural organization with two thioredoxin domains facing each other on top of the dimerization/peptide-binding region. To aid the understanding of the mechanistic significance of thioredoxin domain dimerization and of the peptide-binding cleft of DsbC, we constructed a series of protein chimeras comprising unrelated protein dimerization domains fused to thioredoxin superfamily enzymes. Chimeras consisting of the dimerization domain and the α-helical linker of the bacterial proline cis/trans isomerase FkpA and the periplasmic oxidase DsbA gave rise to enzymes that catalyzed the folding of multidisulfide substrate proteins in vivo with comparable efficiency to E. coli DsbC. In addition, expression of FkpA-DsbAs conferred modest resistance to CuCl(2,) a phenotype that depends on disulfide bond isomerization. Selection for resistance to elevated CuCl(2) concentrations led to the isolation of FkpA-DsbA mutants containing a single amino acid substitution that changed the active site of the DsbA domain from CPHC into CPYC, increasing the similarity to the DsbC active site (CGYC). Unlike DsbC, which is resistant to oxidation by DsbB-DsbA and does not normally catalyze disulfide bond formation under physiological conditions, the FkpA-DsbA chimeras functioned both as oxidases and isomerases. The engineering of these efficient artificial isomerases delineates the key features of catalysis of disulfide bond isomerization and enhances our understanding of its evolution.